Analisis Kontribusi Retribusi Parkir Terhadap Pendapatan Asli Daerah Kabupaten Malang - Rahmawati Widya Putri (Universitas Negeri Malang, 2016)
This study aims to determine how is the contribution, growth, effectivity level of parking retribution towards district own source revenue of Malang Regency in 2010-2014 and how realization of forecasting trends parking fees of Malang Regency in 2015-2019. This type of research is descriptive research with quantitative approach. The data chosen are secondary datas which are realization and targets of parking retribution in Malang Regency as well as realization and targets district own source revenue of Malang Regency region in 2010-2014 period. The results showed (1) The contribution of parking retribution towards district own source revenue of Malang Regency experiences fluctuation. This is caused by the renewal of regional regulation about policy official announcement of parking costs. (2) The growth of parking retribution experiences fluctuation. This is pursuant to realization of parking retribution which is focused only on the targets achievement without considering the history growth of it in previous years. (3) Effectivity level of parking retribution towards district own source revenue of Malang Regency classified effective. (4) The realization trend forecasting parking fees of Malang Regency in 2015-2019 continues to increase. Keywords : region revenue, parking retribution, contribution